Investigating grade R teacher institutional identity presented in policy and expressed through narrative in a time of transition - Long, Roxanne (Rhodes University, Faculty of Education, Department of Education, 2021)
This study investigated Grade R (reception year) teacher institutional identity presented in policy and expressed through teacher narratives. The study was conducted in the context of a major national policy transition that involved the physical and contextual shift of Grade R out of the Early Childhood Development sector and into the formal schooling sector. This study highlighted the way in which this shift has resulted in mixed policy messages, which have implications for Grade R teachers' institutional identities and learning trajectories across their landscapes of practice. The thesis begins by exploring the South African Education context in general as well as the Early Childhood Development context in particular. In order to understand the institutional identities of Grade R teachers as both storied by others (in policy) and by themselves, the study conducted a documentary analysis of policy relating to Grade R teachers and Grade R teacher narrative expressions of their identities. The methodological approach of the study involved a qualitative approach, drawing on grounded theory analytical techniques to closely examine policy documents and teacher generated data gathered through interviews and questionnaires. The study was guided by a sociocultural perspective and drew on three key sociocultural theorists whose work provided complementary perspectives on teacher identity. Sfard and Prusak's (2005) operationalization of identity as narratives was used to define the unit of analysis for the study (i.e. identities as stories). Gee's (2000) definition and conceptualization of institutional identity was supplemented with Wenger-Trayner, Fenton-O'Creevy, Hutchinson, Kubiak, and Wenger-Trayner's (2015) notion of identity as journeying across landscapes of practice. This complementary framing allowed for focused and detailed analysis of policy documents and Grade R teacher identity stories. The study addresses the research gap of an under-representation of identity research in early childhood teacher education and particularly in the South African context. This study is significant as it is the first study of its kind to explore the importance of identity formation for Grade R teachers as newcomers to the formal schooling landscape. Findings from the policy analysis point to mixed messages moving across a spectrum of descriptors from the not yet qualified 'mothers and 'caregivers' to qualified 'specialised' educators. These descriptors have implications for the differentiated roles and responsibilities (institutional identity) of Grade R teachers. The findings from teacher identity narratives highlighted tension in the navigation of the policy promoted institutional identities. Teacher narratives pointed to vastly contrasting experiences of teachers with specialised and qualified institutional teacher identities to those with not yet qualified institutional identities. For the former, there were high levels of confidence in their job security and in terms of recognition received from others. For the latter, however, there was vulnerability in terms of the stability of their jobs and remuneration as well as low levels of recognition from others. The study draws on the findings from the analysis to suggest recommendations for Grade R policy, Grade R teacher education (both inservice and pre-service); as well as Grade R professional development initiatives.
Keywords: Early childhood education -- South Africa; Early childhood education -- Government policy -- South Africa; Child development -- South Africa